Essay: egyptological theme in the works of the Lesia Ukrainka - A. A. Soshnikov (Ukrainian Cultural Studies, 2021)
Dedicated to the problem of modeling the image of Ancient Egypt in the work of Lesya Ukrainka as one of the popular areas of interests of intellectuals of the 19th – early 20th centuries. It was determined that the formation of this image is the result of her solid Egyptological knowledge, formed both through acquaintance with contemporary scientific oriental and Egyptological literature, and through direct study of the ancient Egyptian cultural heritage during her stay in Egypt and visiting its museums and ancient monuments. It is emphasized that the Egyptian essays by Lesia Ukrainka became the first attempt of Ukrainian orientalism to organize knowledge about the East on a Ukrainian mental basis. It is emphasized that the poetry of Lesya Ukrainka on Egyptian themes is the original artistic expression of her "History of the Eastern Peoples", in fact, the views expressed in it on the peculiarities of the development of ancient civilizations.